2008
DOI: 10.1007/s10681-008-9698-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative resistance to downy mildew (Plasmopara halstedii) in sunflower (Helianthus annuus)

Abstract: Downy mildew of sunflower, caused by the Oomycete, Plasmopara halstedii is at present controlled by major resistance genes. However, the pathogen has shown a considerable capacity for changes in virulence and these resistance genes are overcome only a few years after they have been introduced into new sunflower varieties. This paper presents research for quantitative, non-race-specific resistance independent of major genes. The reaction of cultivated sunflower genotypes to field attack by downy mildew was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 23 publications
2
39
0
3
Order By: Relevance
“…To characterize aggressiveness criteria of P. halstedii strains, two INRA inbred lines carrying no Pl gene and known to have different levels of quantitative resistance (Vear et al 2007; Tourvieille de Labrouhe et al 2008) were studied: FU, which has greater resistance in the field and BT, rather susceptible in the field. However, these criteria were used by Sakr (2009a, b) to analyze aggressiveness of P. halstedii strains.…”
Section: Measurements Of Aggressivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize aggressiveness criteria of P. halstedii strains, two INRA inbred lines carrying no Pl gene and known to have different levels of quantitative resistance (Vear et al 2007; Tourvieille de Labrouhe et al 2008) were studied: FU, which has greater resistance in the field and BT, rather susceptible in the field. However, these criteria were used by Sakr (2009a, b) to analyze aggressiveness of P. halstedii strains.…”
Section: Measurements Of Aggressivenessmentioning
confidence: 99%
“…The first is qualitative resistance which is conferred by the major Pl genes and tends to produce a disease-free plant (Tourvieille de Labrouhe et al 2000). The second is quantitative resistance which is controlled by minor genes and tends to impact the rate of disease development (rate reducing) rather than producing a disease-free plant (Tour) -vieille de Labrouhe et al 2008). For qualitative resistance selection pressure, Tourvieille de Labrouhe et al (2010) showed that whatever the method of management (mixture, alternation, and monoculture) of Pl genes, their selection pressure led to appearance of new virulence.…”
Section: Introductionmentioning
confidence: 99%
“…It carried no Pl gene, but is known to a have high level of quantitative resistance (Tourvieille de Labrouhe et al, 2008). The index of aggressiveness of P. halstedii single zoosporangium isolate was calculated as the ration of (percentage infection × sporulation density) / (latent period×dwarfing).…”
Section: Measurement Of Aggressiveness In P Halstedii Single Zoospormentioning
confidence: 99%
“…Indeed, it has been possible to identify up to 35 races, with different virulence patterns (Ahmed et al, 2012). Disease resistance in sunflowers to P. halstedii can be placed in one of two categories, the first is qualitative resistance (Tourvieille de Labrouhe et al, 2000), and the second is quantitative resistance (Tourvieille de Labrouhe et al, 2008).…”
mentioning
confidence: 99%
“…Partial resistance to P. halstedii in high oleic sunflower hybrids has been reported as well by Baldini et al (2006) in Italy. Quite recently, in summarizing their 4-year-study, Tourvieille de Laboruhe et al (2009) suggested that it should be possible to select for non-race-specific downy mildew resistance and to include it in modern varieties. However, since this type of resistance is partial, it may be necessary to combine it with major gene resistance.…”
Section: Sources and Inheritance Of Resistancementioning
confidence: 99%